(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
Comfort has always been one of the engines of progress, forcing human thought to invent more and more new devices to make their lives easier. Since ancient times, people have always sought to arrange their homes in such a way as to maximize comfort with minimal effort. Lighting, like nothing else, affects home comfort. Properly selected light can even affect mood. It can have both positive and negative effects on performance. By adjusting the lighting, you can create an intimate or working environment, calm your thoughts and prepare yourself for sleep, or, conversely, trigger brain activity and wake up. In addition to functionality, light also has a decorative function. By choosing the right brightness and color, you can visually change the interior and create the right atmosphere. That is why proper lighting should be given due attention. Recently emerged smart technologies are gaining popularity around the world. Until recently, smart lighting was considered very expensive, but now it is becoming more affordable. There are many manufacturers, additional functions, and different types of smart lighting. How does smart lighting technology work in the home? You can control the light using either a remote control or voice commands. Newer versions have special apps for smartphones that serve as a kind of remote control. Smart lighting is a lighting technology aimed at increasing the energy efficiency and comfort of using artificial light sources, which is achieved through the use of automated control, light sensors, as well as planning, accentuation, and modern ways of interacting with people and other equipment.